SCAFFOLDING STUDENTSâ INTERACTION WITH TEXTS USING QAR STRATEGY - Sulistyo, Teguh (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2012)
The teaching of reading as a foreign language (EFL reading) in Indonesia aims at enabling students to read and comprehend texts and other materials written in English. Due to the importance and lack of reading skills of students, this study was conducted to overcome the studentsâ difficulties in reading comprehension and encourage students to actively participate in the teaching-learning process through Question-Answer Relationship (QAR) strategy. The findings of the research, taken at Kanjuruhan University of Malang, showed that QAR strategy was worthy to improve the studentsâ reading skills, especially critical and scanning skills, and activate students to participate in the teaching-learning process of reading.Keywords: QAR strategy, reading comprehension skills